Review article: new treatments for advanced differentiated thyroid cancers and potential mechanisms of drug resistance - Hamidi, Sarah; Hofmann, Marie-Claude; Iyer, Priyanka C.; Cabanillas, Maria E.; Hu, Mimi I.; Busaidy, Naifa L.; Dadu, Ramona (Frontiers in Endocrinology, 2023)
The treatment of advanced, radioiodine refractory, differentiated thyroid cancers (RR-DTCs) has undergone major advancements in the last decade, causing a paradigm shift in the management and prognosis of these patients. Better understanding of the molecular drivers of tumorigenesis and access to next generation sequencing of tumors have led to the development and Food and Drug Administration (FDA)-approval of numerous targeted therapies for RR-DTCs, including antiangiogenic multikinase inhibitors, and more recently, fusion-specific kinase inhibitors such as RET inhibitors and NTRK inhibitors. BRAF + MEK inhibitors have also been approved for BRAF-mutated solid tumors and are routinely used in RR-DTCs in many centers. However, none of the currently available treatments are curative, and most patients will ultimately show progression. Current research efforts are therefore focused on identifying resistance mechanisms to tyrosine kinase inhibitors and ways to overcome them. Various novel treatment strategies are under investigation, including immunotherapy, redifferentiation therapy, and second-generation kinase inhibitors. In this review, we will discuss currently available drugs for advanced RR-DTCs, potential mechanisms of drug resistance and future therapeutic avenues.